HUBUNGAN TINGKAT PENGETAHUAN KELUARGA TENTANG KEKERASAN PADA ANAK DENGAN KEJADIAN KEKERASAN PADA ANAK DI PERUMAHAN GRAHA ATHAYA SIAK HULU KAMPAR - INAYATI ULFA (LPPM Universitas Abdurrab, 2018)
ABSTRACT Child abuse is a mistaken treatment of parents, which includes physical, psychological, sexual, and neglect of children. The purpose of this study was to determine the level of family knowledge about violence in children with the incidence of violence in children. This type of research is quantitative with Cross Sectional design. The variables of this study are (independent variable) knowledge and (dependent variable) incidence of violence. Sample size in this research is 60 respondents by using purposive sampling technique.The analysis was done univariat and bivariate. Result of hypothesis test by using chi-square test, obtained p value = 0,429, (p > Î± 0,05), it means Ho is rejected, So that there is a meaningful relationship between the level of family knowledge about violence in children with the incidence of violence in children in Graha Athaya Housing Siak Hulu District Kampar regency. Researchers suggest to nurses and prospective nurses to pay more attention to violence against children in the community because the mental health of children can support the growth and development of children. Researchers also advise people not to use violence in educating children. Keyword : Family, Events, Violence, Knowledge